1988
DOI: 10.1016/s0006-3495(88)83161-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-channel autocorrelation functions: the effects of time interval omission

Abstract: We present a general mathematical framework for analyzing the dynamic aspects of single channel kinetics incorporating time interval omission. An algorithm for computing model autocorrelation functions, incorporating time interval omission, is described. We show, under quite general conditions, that the form of these autocorrelations is identical to that which would be obtained if time interval omission was absent. We also show, again under quite general conditions, that zero correlations are necessarily a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…A linear sequence of shut and open states would predict no correlations. The observed correlation is unlikely to result from distortions introduced by finite time resolution (Ball and Sansom, 1988). In fact, missing brief events as a consequence of limited time resolution may tend to obscure such correlations (Schorge et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A linear sequence of shut and open states would predict no correlations. The observed correlation is unlikely to result from distortions introduced by finite time resolution (Ball and Sansom, 1988). In fact, missing brief events as a consequence of limited time resolution may tend to obscure such correlations (Schorge et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This fact indicates that models which assume that the channelprotein makes transitions only between discrete states of energy are not completely adequate to describe the kinetic process of single-ion channels, at least similar to the one shown here. Markovian models which assume the presence of more than one gate state may show memory and can generate correlations in the open and closed time records (McManus et al, 1985;Ball & Sansom, 1988;Colqhoun & Hawkes, 1987;Steinberg, 1987;Labarca et al, 1985;Jackson et al, 1983). The problem with them is that they are not able to describe fractal long-term correlation, as the Hurst analysis does.…”
Section: Discussionmentioning
confidence: 99%
“…The switching between these states is considered random and the probabilities per unit time (rate constants) of transitions between them depend only on the present state, and not on the previous history of the channel (Colquhoun & Hawkes, 1981, 1982. However, short-term correlation in experimental and simulated data has been shown to exist in some channels (McManus et al, 1985;Ball & Sansom, 1988;Colqhoun & Hawkes, 1987;Steinberg, 1987;Labarca et al, 1985;Jackson et al, 1983) and this can be interpreted to indicate that the channel kinetics is a process with short-term memory. The studies of Toib et al (1998) have shown direct experimental evidence for the existence of memory in the function of ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…However, examination of the NMDA RECEPTOR ACTIVATION data at each individual glutamate concentration shows no obvious trend related to glutamate concentration in the adjacent interval analysis which could have enhanced the correlations observed here. In addition, although the effects of limited time resolution may change the magnitude of any observed correlation, limited time resolution is unlikely to generate an artifactual correlation (Ball & Sansom, 1988).…”
Section: Number Of Apparent Openings Per Clustermentioning
confidence: 99%